Coping Intelligence: Efficient Life Stress Management - Libin, Elena (Frontiers in Psychology, 2017)
Coping Intelligence is defined as efficient individual ways of managing life stress. This paper presents a new assessment instrument named Coping IQ (CIQ; Coping Intelligence Questionnaire). A measure is based on the Multidimensional Positive Coping Model, which includes three cross-cutting parameters that characterize coping strategy as efficient or inefficient, emotional, cognitive or behavioral, and active or passive. Results of the factor analysis verified a basic two-factor structure of the Coping Intelligence with the alternative solutions for efficient and inefficient coping strategies characterized via three basic modalities. The validity of the Coping IQ instrument showed an internal consistency ranging from 0.72 to 0.81.The unified methodology that underlies the new concept of Coping Intelligence, as well as Coping IQ assessment, is applicable for studying both clinical and general populations. CIQ parameters might serve as useful feedback while assessing changes in individual coping repertoire, for CIQ measures strategies that can be modified as a result of life experiences or educational training. Based on the study findings, Coping Intelligence is further defined by a broad repertoire of life skills required to solve successfully everyday stress and life adversities in order to achieve desired goals and maintain physical, mental, and social well-being.